CALCULATION OF THE INTERMOLECULAR BOUND-STATES FOR WATER DIMER - Althorpe, S; Clary, D (1994)
The intermolecular bound states of (H2O)2 are calculated using a simple approach previously found successful for (HF) 2. The monomer bond lengths and bond angles are held fixed, and the angular part of the Hamiltonian is solved variationally at three values of the intermolecular radial coordinate. The results enable comparisons of the tunneling splittings obtained from three potential energy surfaces to be made with experiment. Estimates of three of the intermolecular vibrational frequencies are also obtained. © 1994 American Institute of Physics.